Essential Issues in Stakeholders’ Management: A Critical Perspective on Corporate India - Chakraborty, Gourab (Asian Journal of Empirical Research, 2018)
This paper examines the critical issues faced by the Indian firms in their relationship with their employees (largely workmen) and it analyses the complexity and the enormity of transacting with the government, an important external and derivative stakeholder. Extant literature on stakeholders’ management is yet to singularly and deeply discuss the relationship of the firm with the Government. In fact, in course of this work I failed to come across any western scholar who has recognized the government as an important external and derivative stakeholder. Moreover, the instances that are cited in the text with regard to government policy actions had captured India’s collective consciousness. Indian Public Limited companies were sampled based on their proximal interface with the union government of India.